2016
DOI: 10.1111/iju.13235
|View full text |Cite
|
Sign up to set email alerts
|

Laparoendoscopic single‐site surgeries: A multicenter experience of 469 cases in Japan

Abstract: Objective: To report on a multi-institutional series of non-robotic urological laparoendoscopic single-site surgery in Japan. Methods: Consecutive cases of laparoendoscopic single-site surgery carried out between February 2009 and December 2012 at nine academic institutions were included. We examined the surgical outcomes, including conversion and complications rates. Results: Four hundred and sixty-nine cases were included in the analysis. The most common procedure was adrenalectomy (n = 177) and the second m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 31 publications
(87 reference statements)
0
4
0
Order By: Relevance
“…1,2 The article by Sato et al presents a multi-institutional study evaluating the surgical outcomes of urological LESS surgery, including the safety and feasibility of the procedure, at nine university centers in Japan. 3 The authors retrospectively presented 469 consecutive patients undergoing LESS surgery for a wide range of urological diseases. According to the authors, the study is the second largest series of diverse LESS urological surgery.…”
Section: Editorial Commentmentioning
confidence: 99%
“…1,2 The article by Sato et al presents a multi-institutional study evaluating the surgical outcomes of urological LESS surgery, including the safety and feasibility of the procedure, at nine university centers in Japan. 3 The authors retrospectively presented 469 consecutive patients undergoing LESS surgery for a wide range of urological diseases. According to the authors, the study is the second largest series of diverse LESS urological surgery.…”
Section: Editorial Commentmentioning
confidence: 99%
“…Laparoendoscopic single‐site surgery (LESS) techniques have been widely proposed for various procedures; however, its adoption had been previously limited by its steep learning curve and technical constraints, such as clashing instruments, limited operative space, and difficulties in triangulation 8 . Continuous development and technological progress have allowed recent iterations to overcome these obstacles and shortcomings.…”
Section: Introductionmentioning
confidence: 99%
“…Sato et al reported that 469 single-site surgeries were carried out between February 2009 and December 2012 at nine academic institutions in Japan. Radical prostatectomy was carried out in only six cases [6]. However, adding one or two port, reduced port surgery is easier than single-port surgery.…”
Section: Introductionmentioning
confidence: 99%